Soil, Water and Land Use: II. Understanding Nitrogen Interactions - Angela Schipper; Joseph Schipper; Art Hornsby (EDIS)
Soil, Water and Land Use: II. Understanding Nitrogen Interactions was written by Angela Schipper, Louis Schipper and Art Hornsby of the Soil and Water Science Department, University of Florida. Reviewed June, 2002.